Strengthening Conflict Sensitive Approaches to Climate Change in MENA - Sieghart, Lia Carol; Betre, Mahlette; Mizener, Joseph Allen (World Bank, Washington, DC, 2018)
The Middle East and North Africa (MENA) is among the world’s most vulnerable regions to climate change. The region is projected to experience increasing temperatures, water stress, and instances of extreme weather events, with direct consequences for regional food and water security. The links between climate change and conflict have been much discussed and debated among policy makers and academics alike. There is increasing consensus around a more moderate view that climate change alone will not likely generate conflict, instead, it will more likely serve as a threat multiplier that can put pressure on already scarce resources and exacerbate pre-existing issues, such as political instability, poverty, and unemployment, - underscoring the importance of a conflict-sensitive approach to climate change in this context. The greater use of technology, big data, and advanced modeling present a significant opportunity to inform targeted and appropriate guidance and policy options. With this approach, policymakers and practitioners can be better equipped to anticipate and effectively plan for changes, avoid unintended consequences, while strengthening the long-term viability of the environment and natural resources and encouraging cooperation and strengthened social contract.